Analisis Kemampuan Representasi Matematis Siswa SMP pada Materi Statistika - Endah Silviani; Dian Mardiani; Deddy Sofyan (Mosharafa: Jurnal Pendidikan Matematika, 2021)
AbstrakKemampuan representasi matematis sangat penting dalam pembelajaran matematika, akan tetapi dalam kenyataannya siswa cenderung meniru langkah guru dalam menyelesaikan masalah. Tujuan dari penelitian ini adalah untuk mendeskripsikan  kemampuan representasi verbal,  representasi gambar, dan representasi simbol, serta pemahaman dari siswa SMP pada materi statistika. Penelitian ini menggunakan metode penelitian deskriptif. Kesimpulan yang diperoleh dari penelitian ini adalah pada indikator kemampuan representasi verbal dan indikator kemampuan representasi gambar atau visual ketiga subjek yang diteliti sudah cukup menguasai.  Pada indikator kemampuan representasi simbol hanya dua subjek yang sudah menguasai, sedangkan satu subjek lainya kurang memahami representasi simbol.  Pada pemahaman mengenai materi statistika, rata-rata dari ketiga subjek yang diteliti sudah cukup menguasai materi statistika. Saran penulis bagi guru adalah upayakan guru berusaha memberikan metode dalam penyampaian materi yang membuat siswa bersemangat misalnya memberikan materi melalui video supaya siswa tidak merasa bosan. Analysis of Mathematic Representation Ability of Junior Highschool Students in Statistics Materials AbstractThe ability of mathematical representation is very important in learning mathematics, but in reality, students tend to imitate the teacher's steps in solving problems. The purpose of this study was to describe the ability of verbal representation, image representation, and representation of symbols, as well as an understanding of junior high school students on statistical material. This study uses descriptive research methods. The conclusions obtained from this study are the indicators of verbal representation capabilities and indicators of the capabilities of the representation of the image or visual three subjects studied have been quite mastered. In indicators, the ability of the symbolic representation is only two subjects that have mastered, while the other subjects do not understand the representation of the symbol. In an understanding of statistical material, the average of the three subjects studied has sufficiently mastered statistical material. The author's advice for teachers is to try the teacher trying to provide a method in delivering material that makes students vibrant for example giving material through video so that students don't feel bored.